Efficacy of the conventional deformation analysis based on different strategies on the design stage of the network - Erdogan, Bahattin; Durdag, Utkan Mustafa; Hekimoglu, Serif (TAYLOR & FRANCIS LTD, 2020)
In different Geodetic networks the observations are measured repetitively. These observations, called original observations, are independent. At the design stage of the deformation monitoring network, either the mean value of the original observations or the original observations may be considered. Conventional Deformation Analysis (CDA) is based on the ordinary Least Square Estimation (LSE) that uses the mean value of the original observations. In this paper, the efficacies of results of CDA were investigated for the three different strategies 1o ordinary LSE, 2o LSE with original observations and 3o both LSE with original observations and subnetwork design. To perform the investigation of reliability, leveling network and GPS network were designed, and the mean success rate (MSR) of the methods were computed. The MSRs of the third strategy gets improvements on MSR about 34% for leveling network and 38% for GPS network according to ordinary LSE when three of eight points displaced.
Keywords: Deformation analysis; Mean success rate; Least-squares estimation; Original observations; Levelling network; Subnetwork design; GPS network; TESTS; Engineering; Geology; Remote Sensing